EFISIENSI PROSES DISTRIBUSI BAHAN BAKAR MINYAK DI PT. PERTAMINA (PERSERO) DEPOT PELUMPANG, JAKARTA - Haris Hidayat; Masjraul Hidayat; Dian Anom Baskoro (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The purpose of the study was to find out the efficient way in deciding the route to maximize the fuel distribution from Plumpang depot to every gas station. The method used was qualitative descriptive with saving matrix and nearest neighbor technique analysis. Using the qualitative data to gain information used to solve the problems, the method was able to find out the best route by considering the vehicles’ capacity and demand from each customers. The data were the distance between depot and gas stations, the distance between gas stations, the demand of each customers, and parking area of vehicles’ capacity in the gas stations. The result shows that by using the analysis of saving matrix and nearest neighbor, the minimum distribution route and lessening the time consumed in distributing can be applied.